2009
DOI: 10.1080/20786204.2009.10873834
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient blood glucose management of diabetic patients in a large secondary hospital

Abstract: Background: Diabetes has become a major health problem worldwide, as well as in South Africa. This, coupled with the chronicity of the disease, relate to an increasing burden on health care facilities and an increasing number of hospital admissions of patients suffering from diabetes. Admissions are mostly related to diabetes itself, but the frequency of admissions for problems not related to diabetes is increasing as the prevalence of diabetes increases in the population. Proper inpatient glycaemic management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…This may be due to the fact that 99 % of females were housewives without any proper exercise and food control and thus the prevalence of obesity, a risk factor for developing type 2 diabetes, has been reported to be higher among females. This result is consistent with the results of a study carried out by Van Zyl and Rheeder (6) , which is somewhat different from that observed from other studies, such as Adhikari et al (5) and Tripathi et al (7) . The results of Tripathi et al (7) show that diabetic males (62.5 % ) were in the majority when compared with diabetic females.…”
Section: Discussionsupporting
confidence: 57%
“…This may be due to the fact that 99 % of females were housewives without any proper exercise and food control and thus the prevalence of obesity, a risk factor for developing type 2 diabetes, has been reported to be higher among females. This result is consistent with the results of a study carried out by Van Zyl and Rheeder (6) , which is somewhat different from that observed from other studies, such as Adhikari et al (5) and Tripathi et al (7) . The results of Tripathi et al (7) show that diabetic males (62.5 % ) were in the majority when compared with diabetic females.…”
Section: Discussionsupporting
confidence: 57%